Optimization of Reinforced Aluminium Scraps from the Automobile Bumpers with Nickel and Magnesium Oxide in Stir Casting - V. Vijayan; A. Parthiban; T. Sathish; L. Ponraj Sankar; S. Dinesh Kumar; S. Saravanakumar; Dawit Tafesse (Advances in Materials Science and Engineering)
Here, the investigation is spotlighted on the aluminium alloy from the waste materials of the automobile bumpers which is a reinforced metal matrix composite created with 5 percentage of nickel and 5 percentage of magnesium oxide through the stir casting method. The stir casting process inputs parameters such as pressure of squeezing, time of squeezing, and speed of stirrer which were optimized based on the two mechanical properties’ outcome such as the tensile strength (TS) and Rockwell hardness. There are nine different experiments which were conducted based on the L9 array. The Taguchi method is used to identify the optimum input values for the greatest result of the processing condition by Minitab software. The responses-based parameters were ordered based on the rank identified through the investigational effects. Finally, the optimized input consideration values and the linear equations are recommended for both the considered outputs as conclusions.